The ||accomplished Chess Player an |elementary treatise explaining the game, as played by the London Club and [...] |Morals of Chess by Franklin [...] (Causton Henry Kent jun., 1837)
Essay, introduction to the Rudiments by G. Walker, Teacher; three Games by Philidor, sixty Openings etc. by W. Kenny, Teacher.
not. rkps
Keywords: szachy